Some thecate hydroids (Cnidaria: Hydrozoa) from off New Caledonia collected during KANACONO and KANADEEP expeditions of the French Tropical Deep-Sea Benthos Program - Galea, Horia R.; Schuchert, Peter (European Journal of Taxonomy, 2019)
Thirty-six species of various thecate hydroids occur in two recent, deep-water collections from off New Caledonia. Of these, nine are new, namely Solenoscyphus subtilis Galea, sp. nov., Hincksella immersa Galea, sp. nov., Synthecium rectangulatum Galea, sp. nov., Diphasia alternata Galea, sp. nov., Dynamena opposita Galea, sp. nov., Hydrallmania clavaformis Galea, sp. nov., Symplectoscyphus acutustriatus Galea, sp. nov., Symplectoscyphus elongatulus Galea, sp. nov. and Zygophylax niger Galea, sp. nov. The male and female gonothecae of Caledoniana decussata Galea, 2015, the female gonothecae of Caledoniana microgona Galea, 2015, as well as the gonothecae of both sexes of Solenoscyphus striatus Galea, 2015 are described for the first time. The systematic position of the genera Solenoscyphus Galea, 2015 and Caledoniana Galea, 2015 is discussed on both morphological and molecular grounds, and both are confidently placed within the family Staurothecidae Maronna et al., 2016. In light of the molecular data, the genera Billardia Totton, 1930 and Dictyocladium Allman, 1888 are assigned to the families Syntheciidae Marktanner-Turneretscher, 1890 and Symplectoscyphidae Maronna et al. , 2016, respectively. The previously undescribed gonothecae of Hincksella neocaledonica Galea, 2015, and the male gonothecae of Sertularella tronconica Galea, 2016, were found. Thyroscyphus scorpioides Vervoort, 1993, a peculiar hydroid with putative stem nematothecae, is redescribed and assigned to the new genus Tuberocaulus Galea, gen. nov. Noteworthy new records from the study area are: Tasmanaria edentula (Bale, 1924), Hincksella sibogae Billard, 1918, Dictyocladium reticulatum (Kirchenpauer, 1884), Salacia sinuosa (Bale, 1888) and Billardia hyalina Vervoort & Watson, 2003. Most species are illustrated to facilitate their identification, and the morphology of the new ones is compared to that of their related congeners.